Protein phosphorylation : a practical approach - Hardie, D. G (Oxford University Press, 1999)
Reversible phosphorylation is one of the major mechanisms of controlling protein activity in all eukaryotic cells. This new edition of Protein Phosphorylation: A Practical Approach provides a comprehensive description of current methods used to study protein phosphorylation and the kinases and phosphatases which catalyse it. It includes protocols for studying phosphorylation in intact cells; analysis of signal transduction pathways, kinase specificity, and kinase interactions; assay and purification of kinases and phosphatases; and identification of substrates. Also covered are cloning and expression protocols and advice on the crystallization of kinases and phosphatases. Protein Phosphorylation: A Practical Approach 2e will therefore be of great value to any researcher investigating aspects of reversible protein phosphrylation.
Practical approach series ; 211
Keywords: klinické laboratorní techniky; fosfoproteiny; Clinical Laboratory Techniques; Biochemistry; Phosphoproteins; Proteins; Laboratorní technika; Phosphorylation; proteiny; Biochemie; Proteiny; fosforylace; biochemie